A guide to EU renewable energy policy: comparing Europeanization and domestic policy change in EU member states - Solorio, I.; Jörgens, H. (2017)
The European Union’s renewable energy policy is one of the most ambitious attempts to facilitate a transition towards more sustainable energy systems. This book provides a comprehensive guide to the policy and its implementation. It contains key case studies for understanding how member states have shaped the policy; how the EU has affected the policies of its member states; and how renewable energy policies have diffused horizontally. An analysis of external dimensions is also included. This guide is the first comprehensive attempt to shed light on the complex dynamics of renewable energy promotion in the European multilevel system. Theoretically driven, the study employs Europeanization as an analytical framework for assessing policy change, both at the EU level and in the member states, and compares the development of renewable energy policies in the electricity and transport sectors from the 1980s to the present. Comprising contributions from leading scholars, the book is an indispensible guide for academics, researchers and students interested in EU energy and climate policies in general and EU renewable energy policy specifically as well as practitioners and stakeholders involved in renewable energy policy and climate protection.